Bioaugmentation Effect of Alcaligenes sp.2 and Isolates Bacillus sp.2 on Lowering Used Lubricating Oil- Contaminated Soil pH - Nur Afni; Yuni Ahda (Serambi Biologi, 2020)
Abstract. This study aims to see the effect of biugmentation on pH values on contaminated oil used soil. In this study using Alcaligenes sp.2 isolates. and Bacillus sp.2 which was successfully isolated by Ahda and Fitri (2016). The bacterial formulation is a single isolate of Alcaligenes sp.2, Bacillus sp.2 and the Alcaligenes sp.2 and Bacillus sp.2 consortium. The variation in frequency of biaoaugmentation used in this study was 6 times biotechnology. Calculation of pH values is done once a week and carried out during the 6 weeks of the study period. The results of this study indicate that bioaugmentation influences the pH value of contaminated oil used soil. The type of bacteria that is the fastest in reducing and increasing pH in contaminated oil from used oil is a consortium of Alcaligenes sp.2 bacteria. and Bacillus sp.2.Keywords: Bioaugmentation, Hydrocarbons, pH, Alcaligenes sp.2. and Bacillus sp.2.